Preparation and characteristics of polypropylene composites - Majchrzak, Z.; Lipczyński, J. (Polimery, 2022)
Polypropylene and propylene/ethylene copolymers filled with modified or unmodified mineral fillers were obtained using two methods. In the first one the fillers were introduced in the polymerization process carried out in the presence of TiCl4/AlEt3 catalyst on magnesium support. The other method consisted in mixing of the filler with a polymer and further melting of the whole system. The effects of the type and amount of the filler on the activity of catalytic system (reaction rate) were determined (Fig. 1, 2). The dependences of density and tensile properties of the composites obtained on the method of preparation were investigated (Table 1 and 2). The results show the polymers prepared by melt blending of the polymers with the fillers, both modified and unmodified, show good mechanical properties. What concerns the composites prepared in the polymerization step, only in the case of use of unmodified bentonite the polymer obtained showed good strength properties and lack of catalytic system deactivation. However, organophilized fillers containing polar groups cause decrease in catalyst activity during the polymerization as well as deterioration of mechanical properties of the product.